Reassessment of Expectations as a Comparison Standard in Measuring Service Quality: Implications for Further Research - Parasuraman, A.; Zeithaml, Valarie A.; Berry, Leonard L. (Journal of Marketing, 1994)
The authors respond to concerns raised by Cronin and Taylor (1992) and Teas (1993) about the SERVQUAL instrument and the perceptions-minus-expectations specification invoked by it to operationalize service quality. After demonstrating that the validity and alleged severity of many of those concerns are questionable, they offer a set of research directions for addressing unresolved issues and adding to the understanding of service quality assessment.